The Impact of Students’ Perceptions of Online Learning Environments on Students’ Satisfaction in the Context of Covid-19 Pandemic - Sunipa Ghosh Dastidar (Indonesia Approach Education, 2021)
In the context of the Covid-19 pandemic, the present study aimed to examine students’ perceptions of online learning environments and students’ satisfaction based on their academic stream. The study also investigated the impact of students’ perceptions of online learning environments on students’ satisfaction. A quantitative descriptive survey method was applied. This study included 230 students (130 undergraduate and 100 postgraduate students) from colleges and universities of West Bengal. Online Learning Environments Survey, an adapted and translated (Bengali) version of the Distance Education Learning Environments Survey (DELES) by Scott L Walker (2003), was used for collecting data. For data analysis, statistical techniques, ANOVA and regression analysis were performed. The results revealed significant mean differences among arts, commerce, and science students’ perceptions of online learning environments in the dimensions of student interaction and collaboration, personal relevance, authentic learning, active learning, and student autonomy except in instructor support. Furthermore, a significant mean difference in student satisfaction was found based on the academic stream. The result revealed that overall students’ perceptions of online learning environments had a significant impact on student satisfaction, with student interaction and collaboration being the most significant predictor of all; however, instructor support, active learning, and student autonomy were not found to be significant predictors of student satisfaction.